GENETIC ASPECTS OF ENDOMETRIAL CANCER - V. A. Pushkarev; V. A. Kulavsky; T. V. Viktorova; G. M. Iskhakova; E. V. Kulavsky (Опухоли женской репродуктивной системы)
Whether endometrial cancer (EC) is associated with different allele variants of genes of the detoxification system of xenobiotics has been studied and analyzed. The study has been conducted on a sufficient number of patients (102 and 149 women in the study and control groups, respectively). The methods used have been quite adequate to solve the set task.There are significant differences in the distribution of the frequency of genomes of the GSTM1 gene between patients with EC and the controls (χ2 =3.9, p = 005).Homozygous carriers of GSTP1 gene mutation in EC patients are encountered more frequently in the control group (5.9 and 3.4%, respectively), which shows the increased probability of EC in women with this genotype; heterozygous carriers of mutation with Ile/Val genotype are also identified more frequently in EC patients (47.05 %) than those in the control group (33.5; p = 0.04); the odds ratio was 1.76, which suggests a high risk of EC.